Interpretasi dalam buku “Self Improvement Is it bad or good habbit” : (Kajian Semantik) - Selvy Dwi Anggraini; Marshanda Dwi Ayu Safira; Monica Eskariani; Eni Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to help readers understand the book Self Improvement in the book Is It Bad or Good Habits in interpreting every word that is considered difficult with the aim of making it easier for readers to understand every word conveyed by the author. So it can also attract other readers to read the Self Improvement book. The research method used is semantic study and can help readers understand the meaning of each word. From the research results, there are more than 50 words whose meaning is difficult to understand. To interpret the meaning of each unsolved word, you can use semantic studies. This is the main concern of the discussion, of course the meaning of each word needs to be reinterpreted